2023
DOI: 10.3390/ijms24021578
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic and Non-Estrogenic Disruptor Effect of Zearalenone on Male Reproduction: A Review

Abstract: According to some estimates, at least 70% of feedstuffs and finished feeds are contaminated with one or more mycotoxins and, due to its significant prevalence, both animals and humans are highly likely to be exposed to these toxins. In addition to health risks, they also cause economic issues. From a healthcare point of view, zearalenone (ZEA) and its derivatives have been shown to exert many negative effects. Specifically, ZEA has hepatotoxicity, immunotoxicity, genotoxicity, carcinogenicity, intestinal toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 141 publications
(168 reference statements)
0
19
0
Order By: Relevance
“…In particular, it has been reported that zearalenone shows a higher affinity with ERβ than ERα and acts in the pituitary gland through the non-classical estrogen membrane receptor G protein-coupled estrogen receptor 1 (GPR30) [ 53 ]. In addition, zearalenone is able to bind to albumin and sex hormone-binding globulin, thus enabling its release and entry into target cells via another estrogen pathway [ 12 ]. However, it is also important to note that zearalenone can have adverse effects on human health through both estrogenic and non-estrogenic pathways [ 12 ] and it is not possible to determine whether the observed effects are due to estrogenic or non-estrogenic activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it has been reported that zearalenone shows a higher affinity with ERβ than ERα and acts in the pituitary gland through the non-classical estrogen membrane receptor G protein-coupled estrogen receptor 1 (GPR30) [ 53 ]. In addition, zearalenone is able to bind to albumin and sex hormone-binding globulin, thus enabling its release and entry into target cells via another estrogen pathway [ 12 ]. However, it is also important to note that zearalenone can have adverse effects on human health through both estrogenic and non-estrogenic pathways [ 12 ] and it is not possible to determine whether the observed effects are due to estrogenic or non-estrogenic activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, zearalenone is able to bind to albumin and sex hormone-binding globulin, thus enabling its release and entry into target cells via another estrogen pathway [ 12 ]. However, it is also important to note that zearalenone can have adverse effects on human health through both estrogenic and non-estrogenic pathways [ 12 ] and it is not possible to determine whether the observed effects are due to estrogenic or non-estrogenic activities. Alternaria toxins such as alternariol and alternariol 9-methyl ether, derived from filamentous fungi of the Alternaria genus, exhibit endocrine-disrupting potential as estrogen receptor agonists [ 19 ] and may also activate other steroid receptors, such as the androgen and progesterone receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…113 The hybrid PKS product 82 is analogous to the hormone 17-β-estradiol and capable of competitively binding to the receptors of estrogen influencing the hormone homeostasis. 114 α-Zearalenol (zeranol, Ralgro, α-ZOL, 83 ), a derivative of 82 , is widely used in the US and Canada as an anabolic agent in beef cattle and sheep for growth promotion. 115 As a non-steroidal estrogen, 83 is about four times as estrogenic as 82 , whereas the estrogenic effect of β-ZOL ( 84 ) is about equal to that of 82 .…”
Section: Fungal Pks-derived Natural Productsmentioning
confidence: 99%
“…Biosynthetically, aer the cyclization of 2,3(S)-oxidosqualene (111) into the tetracyclic precursor protosta-17(20)Z,24-dien-3bol (112) by FusA, two sequential oxidations on C-4 and C-16 occur by FusB4 and FusB2, producing 4b-carboxylic acid (113) and 16b-hydroxy-4b-carboxylic acid (114), respectively. Subsequent reactions include acetylation of the C-16 hydroxyl group, triggered by FusD, resulting in 16b-acetoxy-4b-carboxylic acid (115), and oxidation of the C-21 methyl group to carboxylic acid (116) by FusB3.…”
Section: Reviewmentioning
confidence: 99%